INTERVENTION FOR REPLACING MISSING TEETH AT PATIENTS WITH PERIODONTITIS - Mihaela Mitrea; Edlibi Al Hage Walid; Radu Razvan Maxim; Simona Partene Vicoleanu; Gabriela Dumachita Sargu; Niculescu Simona; Liliana Loredana Hurjui; Irina Gradinaru; Cristina Claudia Tarniceriu; Claudia Florea; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2022)
At present, periodontal disease is the main cause of tooth loss, dethroning dental lesions of carious origin. Treatment os always tailored to the case and clinical situation and can range from simple to complex depending on the degree of periodontal damage. The aetiology of periodontitis is multifactorial. Subgingival dental biofilm elicits a host inflammatory and immune response, ultimately leading to irreversible destruction of the periodontium (alveolar bone and periodontal ligament) in a susceptible host. In order to successfully manage periodontitis, dental professionals must understand the pathogenesis, elimination of the causes and reduction of modifiable risk factors and treatment protocols. The technique of immediate implantation hs been widely used to reduce treatment time and bone loss after extraction. Patients with a history of periodontitis represent a unique group of individuals who previously succumbed to a bacterial challenge. Therefore, it was deemed important to address the management and survival rate of implants in these patients.